Water Treatment for Fish Aquaculture System by Biochar-Supplemented Planting Panel System - Sumrit Mopoung; Vijitr Udeye; Supaluck Viruhpintu; Nonglak Yimtragool; Visarut Unhong (The Scientific World Journal)
Rice husk biochars were prepared by carbonization at 400–600°C. The products were analyzed by FTIR, SEM-EDS, BET, and approximate analysis in order to find final products with the best properties and the lowest carbonization temperature. It has been found that the biochar prepared at 500°C, which has 37.86 ± 0.11% yield, 341.0776 m2/g of BET surface area, and 0.136639 cm3/g of micropore volume, is suitable for use as a root supplement in the aquaponic system. The aquaponic systems consist of aquaculture and a hydroponic system with and without biochar supplement. The control experiment consists of an aquaculture and planting panel with biochar supplement disconnected from each other. Tilapia and Chinese morning glory were used for growth studies. The water quality from all aquaculture ponds has also been analyzed at an interval of 10 days for 47 days. The results showed that the growth rates of Tilapia and Chinese morning glory in the aquaponic system with biochar were clearly higher than in the control experiment, which is in accordance with the water quality in each aquaculture pond. However, the growth rates of Tilapia (23.5 g/body vs. 22.7 g/body) and morning glory (3.907 g/stem vs. 2.609 g/stem) in supplemented biochar system tend to be higher than the nonsupplemented biochar system. It has been shown that rice husk biochar can help in treating water in the aquaponic system by increasing the amount of dissolved oxygen in the aquaculture water and conversion of toxic compounds to those beneficial for plant growth.